The Romanian Community in Florence - V.C. Batranu-Pintea; I. Tarba; C. Coman (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
This study aims to create an accurate description of the Romanian Community in Florence, Italy. To do this scientific approach, mixed methods have been used, respectively the questionnaire and interview survey. This paper investigates varied perspectives of how the Romanians in Florence, Italy, are living, spending their free time, working, and celebrating religious (or not) holidays. It is of great interest in the research field to gather as much information as possible about these behaviours and daily life aspects. Especially in this era, where technology has eliminated the limitation of space and time, thus enhancing choices, communicational acts, and other various aspects in favour of people, both in the personal aspect of life, as well as professional aspects.